A case study of cracks in the scientific enterprise: Response to the comments. (16th February 2016) - Dehmer, Matthias; Mowshowitz, Abbe
Abstract : This paper presents the authors' responses to comments on their paper "Cracks in the scientific enterprise" which appears in this issue of Complexity. © 2016 Wiley Periodicals, Inc. Complexity 21: 20–22, 2016